Anxiety During Pregnancy and Postpartum: Course, Predictors and Comorbidity with Postpartum Depression - Radoš, Sandra Nakić (Acta Clin Croat, 2018)
SUMMARY – Previous findings on peripartum anxiety are inconsistent in respect to the prevalence and course of peripartum anxiety with comorbidity of depression. Our aim was threefold: (1) to examine the course of elevated anxiety during pregnancy, immediately after childbirth, and six weeks postpartum; (2) to establish comorbidity of postpartum anxiety and postpartum depression (PPD); and (3) to examine predictors of anxiety 6 weeks postpartum. A sample of women (N=272) who were below the cut-off score for clinical depression during pregnancy were assessed in the third trimester of pregnancy, then 2 days and 6 weeks postpartum. Questionnaires on anxiety, pregnancy specific distress, stress, coping styles, social support, and depression were administered at each assessment. Obstetric data were collected from the participants’ medical records. The estimated rate of high anxiety was 35% during pregnancy, 17% immediately after childbirth, and 20% six weeks postpartum, showing a decrease in anxiety levels after childbirth. Comorbidity of anxiety and PPD was 75%. Trait anxiety and early postpartum state anxiety are significant predictors of postpartum anxiety. Anxiety is a common peripartum psychological disturbance. Anxiety symptoms overlap with PPD, but not completely, indicating that screening for postpartum mental difficulties should include both depression and anxiety.